PREVALENSI GANGGUAN MENSTRUASI SERTA PENANGANANNYA PADA REMAJA - Adriani, Fitri; Suryani, Lilis; Angraeni, Ningsi; Dahlan, Musfira; FITRI (Journal Of Midwifery And Nursing Studies, 2025)
Background: Indonesia as a developing country has a fairly large adolescent population. One of the changes in adolescent girls when they become adults is menstruation, but menstrual disorders are still a common problem with a fairly high incidence, especially in adolescents. As much as 75%. This can be serious if not treated immediately. Objective: to determine the prevalence of menstrual disorders and their treatment in adolescents, especially female students majoring in Midwifery at Almarisah Madani University. Method: This type of research is quantitative research with a descriptive design with a sample of 21 female students. Results: showed that most respondents (71%) experienced menstrual disorders, with details of 38% having abnormal cycles, 5% experiencing abnormal menstrual duration, and 57% experiencing dysmenorrhea. Meanwhile, amenorrhea was only experienced by 10% of respondents. Menstrual disorders found included polymenorrhea, oligomenorrhea, hypomenorrhea, hypermenorrhea, dysmenorrhea, and amenorrhea. This disorder not only affects physical health, but can also affect the psychological condition and quality of life of adolescents, and has the potential to cause long-term health problems such as infertility. Treatment for adolescents is generally non-pharmacological, including warm water compresses, rest, stress management, improving diet and sleep patterns, and taking painkillers independently.